Diseño de un sistema electromecánico para controlar derrames de aceites en transformadores de potencia (2022)
In this project, the design of the control and automation for the oil spill system of a power transformer is argued, as a protection measure against possible damages in the transmission substations, which will have as main objective to optimize the response times for the prevention of disasters due to oil spills in electrical substations. For this, a series of queries is made of the main parts that make up a power transformer, the regulations that regulate them and the technical specifications of all the elements that it contemplates, with this the sufficient bases are obtained to carry out the project in the most appropriate way. , with the least possible risk to the equipment and operators. This design is reflected in plans which are also integrated into those of a transformer and is simulated with an application that allowed obtaining wiring tables, list of devices, list of materials, to determine the costs and step by step of the operation.